Prevention of Aging and Improvement of Longevity and Life-Span in D-Galactose Induced Aging Rats After Treatment with the Biofield Energy Per Se and Biofield Treated Proprietary Test Formulation - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (Journal of Aging Research And Healthcare, 2020)
The study was aimed to investigate the potential benefits of the Consciousness Energy Healing Treatment (the Trivedi Effect®) per se and Biofield Energy Healing treated novel test formulation in male Sprague Dawley rats for their antiaging activity by monitoring aging biomarkers such as brain-derived neurotrophic factor (BDNF), silent information regulator-1 (SIRT-1), and klotho protein. The test formulation was distributed into two parts. First part did not provide any Biofield Energy Treatment was denoted as the untreated sample, however the second part was received Biofield Energy Healing Treatment by a renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi and defined as the Biofield Energy Treated sample. In this experiment, nine groups (n=10) were assigned, in which four were preventive maintenance groups. Among them, three groups of animals were also received Biofield Energy Healing Treatment per se (at day -15). BDNF was significantly increased by 25.83%, 19.35%, and 14.67% in the Biofield Energy Treated test formulation (G5), Biofield Energy Treatment per se at day -15 (G6), and Biofield Energy Treatment per se to animals plus Biofield Treated test formulation from day -15 (G8), respectively as compared to the disease control (G2) group. Moreover, expression of SIRT-1 protein was increased by 14.63% in the G5 group than the untreated test formulation (G4) group. Additionally, SIRT-1 activity was increased by 39.7%, 32.5%, 15.9%, and 136% in the G6, Biofield Energy Treated test formulation at day -15 (G7), G8, and Biofield Treatment per se (day -15) to animals plus untreated test formulation (G9) groups, respectively than the G4 group, while it was increased by 57.3% in the G9 group as compared to the G2 group. Besides, Klotho protein in kidney homogenate was significantly increased by 16.67% in the G5 group as compared to the G2 group. Altogether, the results showed a significant improvement of longevity mediators and antiaging biomarkers in the preventive maintenance groups. Therefore, results envisaged the significant slowdown of aging-related disorders and other complications in the preventive Biofield Energy Treatment group per se and/or Biofield Energy Treated Test formulation groups (viz. G6, G7, G8, and G9) comparatively with the disease control group and could be utilized against various aging-related disorders like Alzheimer's disease, hypertension, osteoporosis, cataracts, type 2 diabetes, cancer, etc. along with it could be used to extend the life-span, stress and immune-related disorders.
Keywords: Anti-aging; BDNF; Biofield Treatment; Consciousness Energy Healing; Klotho; SIRT-1; The Trivedi Effect®